Game-based learning and self-reflection assessment: helping grade 8 students cope with mathematical anxiety - Jinky B. Abangan; Marnny Grecile R. Datu and Jay May M. Roxas. 4 0 16; 5 (2016)
ABSTRACT: The purpose of this study is to determine the students level of performance in problem solving in mathematics, and to find out the challenges encountered by the students. It also aimed to help students enhance their performance and overcome the said challenges using George Polya's four-step plan and the three different strategies in solving word problem. The data sources for this study are pre-survey and pre-test for the challenges the students face and the level of performance in problem solving before the intervention, post-survey and post-test for the challenges the students face and the level of performance after the intervention, and the informal interview with the class Mathematics teacher to confirm the gathered data. The students thought that they rarely face the challenges in problem solving but gave a below average level of performance in the initial problem solving. In the end, the students confirmed that there are challenges that they had encountered and was overcome together with the improvement of their level of performance with the help of George Polya's four-step plan and challenges.
Thesis: (Bachelor of Secondary Education with Specialization in Mathematics) -Pamantasan ng Lungsod ng Maynila, 2016.
Keywords: 2 -- 0; 6; 20; 20; 2